ANALISIS MOTIVASI BELAJAR MAHASISWA PADA PERKULIAHAN KALKULUS DIFERENSIAL - Hajerina, Hajerina; Nursupiamin, Nursupiamin; Dg. Matona, Moh. Fadly A. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to analyse student learning motivation in differential calculus lectures. The method used in this study is the qualitative-descriptive method. The results showed that the average of the six indicators of learning motivation was 3.00, in the very good category